Insight into Coordination of Uranyl Ions with N, N′‐bis(2‐five‐membered heterocyclidene)‐1, 8‐anthradiamines. (14th April 2019) - Long, Li‐yu; Tao, Peng; Li, Tian‐liang; Wu, Si; Kong, Xiang‐he; Liao, Li‐fu; Xiao, Xi‐lin; Nie, Chang‐ming
Abstract : To find new adsorbents for uranyl ions, the density functional theory (DFT) was adopted to design a series of new ligands containing an anthracene and two five‐membered heterocycles with nitrogen family nonmetal elements (N, P, As) or oxygen family nonmetal elements (O, S, Se, Te), for example, ligands N, N′‐bis(2‐five‐membered heterocyclidene)‐1, 8‐anthradiamines (BFHADAs). Then the uranyl ions were coordinated with BFHADAs to generate five new coordination complexes (Uranyl‐BFHADAs) with heteroatoms N, S, As, Se and Te, respectively. The five‐membered heterocyclic rings of Uranyl‐BFHADA with oxygen atoms were broken under the structural optimization and Uranyl‐BFHADA with heterocyclic atoms P was not obtained. Several structures and property parameters of the ligands BFHADAs (containing heteroatoms N, S, As, Se and Te) and their uranyl complexes Uranyl‐BFHADAs were theoretically investigated and analyzed. The results showed that uranyl ions could form stable coordination complexes with these five BFHADAs. The formed bonds between uranyl ions and the heteroatoms in BFHADAs were coordination bonds rather than other types of bonds. These results could provide insightful information and theoretical guidance for the coordination of uranyl with the atoms N, S, Se, As and Te in other ligands. Abstract : A series of new ligands N, N′bis(2‐five‐membered heterocyclidene)‐1, 8‐anthradiamines (BFHADAs), containing an anthracene and two five‐membered heterocycles, were designed. Then the uranyl ions were coordinated with BFHADAs to generate five coordination complexes (Uranyl‐BFHADAs). The results showed that uranyl ions could form stable coordination complexes with BFHADAs. These results could provide insightful information and theoretical guidance for the coordination of uranyl ions with the atoms N, S, Se, As and Te in other ligands.